NONVERBAL COMMUNICATION IN GUILLERMO DEL TORO’S MOVIE: “THE SHAPE OF WATER” - Syam, Syafril Efendy; Abdullah, Abdullah; Halim, Abd. (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research is entitled Nonverbal Communication in Guillermo Del Toro's Movie: “The Shape of Water”. A movie, also known as a movie, is a form of visual storytelling that typically involves a series of images and sounds that are presented to an audience in order to convey a narrative or message. The purpose of this research is to examine the nonverbal communication in the